Analyzing Influence of Ignition Gas Flow Pipe of Igniter on Working Process (Xibei Gongye Daxue Xuebao, 2018)
Based on gas dynamics and computational fluid dynamics, the numerical simulation of the steady-state flow field of igniter working in the two conditions was conducted with FLUENT. The numerical simulation results were validated by experiments. Influences of ignition gas flow pipe on the igniter's working performance were analyzed on the basis of test validation. The analysis results show that the combustion chamber pressure has atmospheric pressure and that the igniter works with ignition gas flow pipe. The velocity of throat is lower than the speed of sound and the sonic position moves to the position of ignition gas flow pipe; the velocity, pressure and temperature of throat increase; but the flux, pressure and temperature of outlet decrease. Under the different conditions of combustion chamber pressure, the outlet velocity, pressure, temperature and flux have a stable section; but the flux decreases.